Siginjei Museum Halal Tourism Management - Simarmata, Jonner; Almaududi, Said; Pratiwi, Heni (International Journal of Multidisciplinary Sciences and Arts, 2024)
The museum is a place to store historical objects, the objects in the museum are historical heritage objects that should be preserved, so that the Indonesian state does not forget the services of the heroes who defended their homeland. The aim of establishing a museum is so that citizens do not forget the history of their nation. Halal tourism itself is expected to be an alternative for Muslim and non-Muslim tourists to travel and fulfill their spiritual needs. This research is field research carried out at the Siginjei Jambi Museum because it is about halal tourism. This type of research is descriptive using a qualitative approach because the data produced is in the form of descriptions. Data collection techniques used in this research were observation, interviews, documentation and literature. The research results of the Siginjei Museum include halal tourism, looking at the facilities it has, such as a prayer room, a toilet, a comfortable place and providing value about the history of the Jambi people's struggle against colonialism and as a goal for school children to learn about the history of Jambi and broaden their knowledge. In terms of service, the Siginjei Museum has done its best, such as preparing a guide to tour the museum and explain the history of each object in the museum.